(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Amongst all psychiatric ailments in school-age children, eating disorders (ED) receive the negligible attention and have the possibility to encounter serious morbidity. Due to their many different forms, EDs in young children are very challenging to diagnose. Invariably, numerous co-morbid psychiatric diagnoses, especially body image issues, self-esteem concerns are more common in children and young adults with ED. In this study, children between the ages of 8 and 13 were evaluated for their prospect of acquiring an early-onset eating disorder (EOED) and their preponderance of experiencing a negative body image. We also intended to investigate if body image issues and BMI were related to EOED.A cross-sectional study was conducted on 133 kids (75 boys and 58 girls) in the pediatric outpatient department of a tertiary care medical college in Chennai who were between the ages of 8 and 13. After receiving informed written agreement, the Socio-demographic Proforma, Children's Eating Attitudes Test-26 (Ch-EAT 26), and Body Shape Questionnaire-8C were administered. Statistical methods namely Pearson correlation and chi-square test were used. Children were more likely than adults to be at hazard for enduring eating disorders early on (10.2% vs. 39.8%). The likelihood of eating disorders, concerns about one's body form, and body mass index were found to have a tepidly positive association. Young children have a high chance of developing early eating disorders, which offers insight into effective intervention options.